Lean for the process industries : dealing with complexity - King, Peter L. (Taylor & Francis, Routledge, 2019)
Compared to its widespread implementation across almost all areas of production, Lean improvement efforts lag within the process industries. While many innovators have successfully applied Lean principles to these industries during the past three decades, most of those pioneering efforts were never recorded to guide the improvement efforts of others. Drawing on more than 40 years of application experience at one of the world's largest chemical and materials manufacturers, coupled with 10 years in private practice, Peter King corrects this void by providing the first comprehensive resource written explicitly for change agents within the process industries. Focusing on areas where the improvement needs of the process industry differ from parts assembly manufacturing, Lean for the Process Industries: Dealing with Complexity, Second Edition: Covers each of the eight wastes commonly described in Lean literature, looking at how they manifest themselves in process operations. Explains how to adapt value stream mapping for process operations. Shows how to identify the root causes of bottlenecks, and how to manage them to optimize flow until they can be eliminated. Provides practical techniques to overcome the barriers which have prevented the application of Cellular Manufacturing to process operations. Discusses the role of business leadership in a Lean strategy, describing both enabling and counter-productive management behaviors Since the publication of the first edition of this book, Peter King has been busy consulting with food, beverage, gasoline additive, and nutraceutical companies--these new experiences have broadened his perspectives on certain Lean processes and have given him a richer set of examples to discuss in this new edition. While Value Stream Mapping is a very powerful tool to understand flow, bottlenecks, and waste in an operation, the traditional format as presented in many other books does not describe all of the data required to fully understand process flow and its detractors. This new edition highlights the necessary additions with examples of why they are useful. Product wheel scheduling achieves production leveling in a far more comprehensive and effective way than traditional heijunka methods. This edition has a more thorough description of the wheel concept and design steps, and more examples from actual applications.